Low back pain prevalence and risk factors in Italian adolescent male soccer players: results from an online survey - Cugusi, L.; Manca, A.; Fischbach, E.; Secci, C.; Bergami, M.; Gobbo, S.; Di Blasio, A.; Montella, A.; Bandiera, P.; Deriu, F. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The purpose of this retrospective survey was to analyze the prevalence of low back pain (LBP) among Italian adolescent soccer players, and to identify potential risk factors. METHODS: Participants were requested to answer an online survey based on the standardized Nordic questionnaires for musculoskeletal symptoms. RESULTS: Data were obtained from 204 male soccer players aged 14-17 years competing at the national and regional level. More than half of the players had experienced LBP in their lives. One-way ANOVA revealed that the players with LBP were taller, heavier and with a higher BMI (all P values<0.00001). When considering the playing position, ANOVA revealed that 14-15 years-old strikers displayed higher LBP scores than all other roles (all P values<0.05). Accordingly, strikers were exposed to a higher risk of LBP than midfielders (RR=1.48; 95% CI: 1.10-2.01; P=0.01) and goalkeepers (RR=1.48; 95% CI: 1.02-2.971; P=0.04), but not defenders (RR=1.23; 95% CI: 0.93-1.63; P=0.15). Within the 14-15 age-class, strikers were, again, those most exposed to LBP risk (all P values<0.05). CONCLUSIONS: Anthropometric and soccer-related features should be monitored to ensure early identification of potential risk factors for LBP. This information should be considered along with the specific playing position as strikers emerged as the roles most exposed to LBP risk.